2012
DOI: 10.4103/2152-7806.102945
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from sports-related concussion: Days to return to neurocognitive baseline in adolescents versus young adults

Abstract: Background:Sports-related concussions (SRC) among high school and collegiate athletes represent a significant public health concern. The Concussion in Sport Group (CIS) recommended greater caution regarding return to play with children and adolescents. We hypothesized that younger athletes would take longer to return to neurocognitive baseline than older athletes after a SRC.Methods:Two hundred adolescent and young adult athletes who suffered a SRC were included in our clinical research cohort. Of the total pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 25 publications
2
68
2
2
Order By: Relevance
“…The history group showed a larger increase in arousal, as reflected by a greater EDA response relative to the no-history group, without a decrement in task performance. Our results are similar to those of researchers [4][5][6][7] who noted that participants with PFC hyperactivation achieved similar behavioral outcomes on a working-memory task.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The history group showed a larger increase in arousal, as reflected by a greater EDA response relative to the no-history group, without a decrement in task performance. Our results are similar to those of researchers [4][5][6][7] who noted that participants with PFC hyperactivation achieved similar behavioral outcomes on a working-memory task.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, short-term memory processes may not fully recover by 6 months after a concussion. N umerous authors [1][2][3][4][5] have identified short-term cognitive impairments resulting from concussion. Affected cognitive processes include attention, memory, and executive function.…”
mentioning
confidence: 99%
“…These studies, relating neurocognitive deficits and return to neurocognitive baseline scores, have provided some of the only age-related data on SRC outcome and have produced inconsistent results regarding time to return to neurocognitive baseline. 4,16,32,34 Due to conflicting findings, further categorization is needed to stratify the effect of age on SRC. Our study aimed to further elucidate age disparities in concussion management by analyzing symptoms post-SRC.…”
Section: Discussionmentioning
confidence: 99%
“…20 More recent evidence suggests that children and adolescents are more likely to endure prolonged symptom recovery [21][22][23] and are more vulnerable to poor outcomes. 24,25 Moreover, neuroimaging studies show persistent structural and functional changes in the brain following mild TBI in children.…”
Section: Introductionmentioning
confidence: 99%